PENGARUH TERAPI ZINGER OFFICINALE TERHADAP INTENSITAS NYERI LOW BACK PAIN DI POSYANDU MARGOMULYO DESA NGRANCAH KECAMATAN GRABAG - MARGONO MARGONO (Jurnal Keperawatan Muhammadiyah, 2016)
Objective: to analyze the effect of Zingiber officinale to decrease the level of pain in patients with Low Back Pain (LBP). Methods: This study design is Quasi Experiment with using the draft "pretest-posttest Design" Results: Evaluation after the intervention occurred during two weeks a significant reduction in pain intensity with pain intensity scale rarely with light. Conclusion: Zingiber officinale therapy can be one of the complementary therapies in nursing care patients with LBP. This study shows that Zingiber officinale can reduce pain intensity.